2013
DOI: 10.1128/aem.00061-13
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic Growth of Bacterial and Archaeal Ammonia Oxidizers in Freshwater Sediment Microcosms Incubated at Different Temperatures

Abstract: Both bacteria and archaea potentially contribute to ammonia oxidation, but their roles in freshwater sediments are still poorly understood. Seasonal differences in the relative activities of these groups might exist, since cultivated archaeal ammonia oxidizers have higher temperature optima than their bacterial counterparts. In this study, sediment collected from eutrophic freshwater Lake Taihu (China) was incubated at different temperatures (4°C, 15°C, 25°C, and 37°C) for up to 8 weeks. We examined the active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 59 publications
11
29
0
Order By: Relevance
“…This observation was true for soils that had never been cropped or N fertilized, as well as for adjacent cropped soils of the same soil series that are regularly cultivated and N fertilized. Although it is unknown if the mechanism of octyne inhibition may itself be temperature-dependent, the temperature niche separation determined with the octyne method agrees with previous studies that found differences in AOA and AOB amoA gene abundances or differential labeling with 13 CO 2 in response to different incubation temperatures (Avrahami et al, 2011;Wu et al, 2013;Zeng et al, 2014), and with the isolation of soil AOA that grow optimally at 35-40°C (Tourna et al, 2011;Kim et al, 2012;Lehtovirta-Morley et al, 2014. Some of these AOA isolates were obtained at an initial cultivation of 37°C (Lehtovirta-Morley et al, 2011Tourna et al, 2011); however, another isolate was initially enriched at 25°C (Kim et al, 2012).…”
Section: Significance Of the Model Resultssupporting
confidence: 73%
“…This observation was true for soils that had never been cropped or N fertilized, as well as for adjacent cropped soils of the same soil series that are regularly cultivated and N fertilized. Although it is unknown if the mechanism of octyne inhibition may itself be temperature-dependent, the temperature niche separation determined with the octyne method agrees with previous studies that found differences in AOA and AOB amoA gene abundances or differential labeling with 13 CO 2 in response to different incubation temperatures (Avrahami et al, 2011;Wu et al, 2013;Zeng et al, 2014), and with the isolation of soil AOA that grow optimally at 35-40°C (Tourna et al, 2011;Kim et al, 2012;Lehtovirta-Morley et al, 2014. Some of these AOA isolates were obtained at an initial cultivation of 37°C (Lehtovirta-Morley et al, 2011Tourna et al, 2011); however, another isolate was initially enriched at 25°C (Kim et al, 2012).…”
Section: Significance Of the Model Resultssupporting
confidence: 73%
“…Most of these studies have focused on autotrophy and ammonia oxidation in various environments such as rice paddies (Lu and Conrad, 2005), soils (Adair and Schwartz, 2011;Pratscher et al, 2011;Lu and Jia, 2013) and in freshwater sediment (Wu et al, 2013). However, there are also reports of heterotrophic activity from an acidic fen (Hamberger et al, 2008) and an estuarine setting in the UK (Webster et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many microbial community studies have evaluated the effect of warming on overall community structure and on specific metabolic processes such as respiration (for example, Zogg et al, 1997;Finke and Jørgensen, 2008;Rose et al, 2009;Yergeau et al, 2012;Lindh et al, 2013;Wu et al, 2013;von Scheibner et al, 2014). Far fewer studies have comprehensively assessed functional responses across the entire community (for example, using 'omic' approaches (Luo et al, 2013;Toseland et al, 2013) or functional gene arrays (Yergeau et al, 2012;Tu et al, 2014)).…”
Section: Introductionmentioning
confidence: 99%